Prime osservazioni sulla proposta di regolamento dell’Unione Europea in materia di intelligenza artificiale (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Artificial Intelligence has great potential in all areas of our lives, but it also presents risks for fundamental rights and the rule of law. The European Union is trying to create a balanced regulatory framework between the pros and cons of AI. On 21 April 2021 EU published a comprehensive proposal for an AI regulation, which should protect and promote European rights and values, without impeding the technological, industrial, and commercial development of AI. This article aims to give a first analysis of the proposal, focusing on its main positive and negative aspects.
Keywords: Artificial Intelligence; European Union Law; Fundamental Rights; Proposal for a Regulation on AI